Thermosetting Paste
Patent Information
- Application Number
- JP2022057098
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-30
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2042-03-30
AI Technical Summary
【0019】 ここに開示される熱硬化性ペーストの一態様では、25℃におけるCasson降伏値が120Pa以下である。これによって、熱硬化性ペーストの成形性を向上させることができるため、表面が平滑な電極を容易に形成できる。
Smart Images

Figure 0007640489000001 
Figure 0007640489000002 
Figure 0007640489000003
Abstract
Description
[Technical field]
[0001] The technology disclosed herein relates to a thermosetting paste. [Background technology]
[0002] Electrodes of electronic components (such as terminal electrodes of solar cell cells) are formed, for example, by printing a conductive paste on a substrate and then curing the paste. One example of this type of conductive paste is a thermosetting paste. This thermosetting paste contains conductive particles such as silver particles (Ag particles) and a thermosetting component such as an epoxy resin. This thermosetting paste is cured by a heat treatment at a relatively low temperature (for example, 400° C. or lower) and does not require a high-temperature firing treatment. For this reason, the thermosetting paste is suitably used in the manufacture of electronic components that use substrates with low heat resistance (such as resin substrates). Patent documents 1 and 2 are examples of this thermosetting paste. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 5281529 [Patent Document 2] Patent No. 6092754 Summary of the Invention [Problem to be solved by the invention]
[0004] Incidentally, various performances are required for electrodes obtained by hardening a thermosetting paste. First, from the viewpoint of the electrical performance of electronic components, the electrodes after the paste is hardened are required to have low electrical resistance. Also, the electrodes are required to have excellent high-temperature reliability so that they do not deform or denature even when exposed to a high-temperature environment. Next, in consideration of the durability of electronic components, the electrodes are required to have excellent adhesion to the substrate. The technology disclosed herein aims to improve these performances and provide a thermosetting paste capable of forming high-quality electrodes. [Means for solving the problem]
[0005] In order to achieve the above object, the technology disclosed herein provides a thermosetting paste having the following composition.
[0006] The thermosetting paste disclosed herein contains at least (A) scaly Ag particles, (B) spherical Ag particles, (C) a thermosetting component, (D) a silane coupling agent, and (E) an organic solvent. The scaly Ag particles (A) of the thermosetting paste have a particle size distribution based on a volumetric basis based on a laser diffraction / scattering method, and the D scaly Ag particles are 50% of the total particle size from the smallest particle size. 50 The particle size is 4 μm or more and 10 μm or less, and the content is 30 parts by weight or more and 80 parts by weight or less when the total weight of the Ag particles is 100 parts by weight. 50 The particle size is 1.5 μm or more and 2.5 μm or less, and the BET specific surface area is 0.5 m 2 / g or less. Furthermore, the (C) thermosetting component contains a novolac type epoxy resin that is solid at 25°C, a curing agent, and a curing accelerator, and the content is 10 parts by weight or more and 15 parts by weight or less when the total weight of the Ag particles is 100 parts by weight. And the (D) silane coupling agent is a silane coupling agent having a polysulfide group, and the content is 0.1 parts by weight or more and 0.6 parts by weight or less when the total weight of the Ag particles is 100 parts by weight.
[0007] First, the thermosetting paste disclosed herein contains two types of Ag particles, namely, scaly Ag particles and spherical Ag particles. When this thermosetting paste is thermally cured, the scaly Ag particles are densely arranged on the surface side of the cured electrode, and the Ag particles are easily in contact with each other inside the cured electrode. In the thermosetting paste disclosed herein, the D of the scaly Ag particles 50The particle size is set to 4 μm or more and 10 μm or less. Scaly Ag particles with such a particle size are likely to form contacts between Ag particles in the electrode after hardening, so that they can form a suitable conductive path in the electrode and contribute to reducing electrical resistance. In the thermosetting paste disclosed herein, the content of the scaly Ag particles is set to 30 parts by weight or more when the total weight of the Ag particles is 100 parts by weight. This allows the resistance reducing effect of the scaly Ag particles to be properly exhibited.
[0008] On the other hand, the bottom side of the electrode after curing is mainly composed of a mixture of spherical Ag particles and a thermosetting component. This improves the adhesion of the electrode to the substrate. Furthermore, in the thermosetting paste disclosed herein, the D 50 The particle size is set to 1.5 μm or more, and the BET specific surface area is set to 0.5 m 2 / g or less. This makes it possible to prevent a plurality of spherical Ag particles from agglomerating together, which would otherwise reduce the contact area between the spherical Ag particles and the thermosetting component. As a result, the adhesiveness of the electrode can be further improved. In addition, in the thermosetting paste disclosed herein, the content of the scaly Ag particles relative to the total weight of the Ag particles is set to 80 parts by weight or less. This makes it possible to make the content of the spherical Ag particles 20 parts by weight or more, so that the adhesiveness improving effect of the spherical Ag particles is appropriately exhibited.
[0009] Next, the thermosetting component of the thermosetting paste disclosed herein contains a novolac type epoxy resin that is solid at 25°C. It has been confirmed by experiments that a paste containing an epoxy resin of such a configuration exhibits a high glass transition point after thermal curing. This suppresses deformation of the electrode in a high-temperature environment, thereby improving the high-temperature reliability of the electrode. In addition, in the thermosetting paste disclosed herein, the content of the thermosetting component (the total content of the epoxy resin, the curing agent, and the curing accelerator) relative to the total weight of the Ag particles is set to 10 parts by weight or more. This makes it possible to prevent a decrease in adhesiveness due to a shortage of the thermosetting component. Meanwhile, in the thermosetting paste disclosed herein, the content of the thermosetting component is set to 15 parts by weight or less. This makes it possible to suppress an increase in electrical resistance due to an excessive addition of the thermosetting component.
[0010] The thermosetting paste disclosed herein uses a silane coupling agent (sulfide-based silane coupling agent) having a polysulfide group. A typical silane coupling agent bonds to both inorganic particles (Ag particles) and thermosetting resin (epoxy resin), and contributes to improving the adhesiveness of the electrode after curing. However, according to the inventor's experiments, it has been confirmed that the sulfide-based silane coupling agent has a different effect that other silane coupling agents do not have, that is, reducing the resistance of the electrode after curing. Although it is not intended to limit the technology disclosed herein, it is expected that the resistance reducing effect of the sulfide-based silane coupling agent is due to the action of increasing the contact points between Ag particles during the curing process. In the thermosetting paste disclosed herein, the content of the silane coupling agent is set to 0.1 parts by weight or more. This allows the resistance reducing effect and adhesiveness improving effect of the sulfide-based silane coupling agent to be properly exhibited. On the other hand, from the viewpoint of suppressing an increase in resistance due to a relative decrease in the content of Ag particles, the content of the silane coupling agent in the thermosetting paste disclosed herein is set to 0.6 parts by weight or less.
[0011] As described above, the thermosetting paste disclosed herein can form high-performance electrodes that are excellent in electrical resistance, high-temperature reliability, and adhesiveness.
[0012] In one embodiment of the thermosetting paste disclosed herein, the (A) scaly Ag particles have an average aspect ratio of more than 1.5 and not more than 10. The scaly Ag particles having such a configuration are easily arranged on the surface side of the electrode after curing, and therefore the electrical resistance of the electrode can be more suitably reduced.
[0013] In one embodiment of the thermosetting paste disclosed herein, the (A) scaly Ag particles have an ignition loss (Ig-loss) of 0.5 wt% or less when heated from room temperature to 600° C. This improves the moldability of the paste, making it easy to form electrodes with smooth surfaces.
[0014] In one embodiment of the thermosetting paste disclosed herein, the (A) scaly Ag particles have a tap density of 4 g / ml or more and 7 g / ml or less, which improves the moldability of the paste and makes it easy to form an electrode with a smooth surface.
[0015] In one embodiment of the thermosetting paste disclosed herein, the (B) spherical Ag particles have an average aspect ratio of 1 or more and 1.5 or less. Since the spherical Ag particles having such a configuration are likely to be arranged on the bottom surface side of the electrode after curing, the adhesiveness of the electrode can be more suitably reduced.
[0016] In one embodiment of the thermosetting paste disclosed herein, the (B) spherical Ag particles have a tap density of 5 g / ml or more and 7 g / ml or less, which can further suitably improve the adhesiveness of the electrode after curing.
[0017] In one embodiment of the thermosetting paste disclosed herein, the novolac epoxy resin includes at least one selected from phenol novolac epoxy resin, cresol novolac epoxy resin, naphthol novolac epoxy resin, naphthol-phenol co-condensed novolac epoxy resin, and naphthol-cresol co-condensed novolac epoxy resin, thereby forming an electrode with even better high-temperature reliability.
[0018] In one embodiment of the thermosetting paste disclosed herein, the silane coupling agent (D) is selected from the group consisting of bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(4-triethoxysilylbutyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(2-triethoxysilylethyl)trisulfide, bis(4-trimethoxysilylbutyl)trisulfide, and bis(3-triethoxysilylpropyl)tetrasulfide. The sulfide-based silane coupling agent contains at least one selected from the group consisting of bis(2-triethoxysilylpropyl) disulfide, bis(2-triethoxysilylethyl) disulfide, bis(4-triethoxysilylbutyl) disulfide, bis(3-trimethoxysilylpropyl) disulfide, bis(2-trimethoxysilylethyl) disulfide, bis(4-trimethoxysilylbutyl) disulfide, 3-trimethoxysilylpropyl-N,N-dimethylthiocarbamoyl tetrasulfide, and 2-triethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide. These sulfide-based silane coupling agents can preferably exhibit both a resistance reducing effect and an adhesion improving effect.
[0019] In one embodiment of the thermosetting paste disclosed herein, the Casson yield value at 25° C. is 120 Pa or less. This can improve the moldability of the thermosetting paste, making it easy to form an electrode with a smooth surface. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] An embodiment of the technology disclosed herein will be described below. Note that matters other than those specifically mentioned in this specification and necessary for implementing the technology disclosed herein (e.g., a means for preparing a paste, a means for printing a paste on a substrate, etc.) can be implemented based on the technical content taught by this specification and the general technical common sense of a person skilled in the art in the relevant field. Note that the expression "A to B" indicating a numerical range in this specification means A or more and B or less.
[0021] 1. Thermosetting paste The thermosetting paste is cured by heat treatment to form a film-like body (electrode) exhibiting electrical conductivity. The thermosetting paste disclosed herein contains at least (A) scaly Ag particles, (B) spherical Ag particles, (C) a thermosetting component, (D) a silane coupling agent, and (E) an organic solvent. The components of the thermosetting paste are described below.
[0022] (A) Scale Ag particles The thermosetting paste disclosed herein contains at least two types of Ag particles, namely, scaly Ag particles and spherical Ag particles. These Ag particles become conductive components in the electrode after the paste is cured. In this specification, "Ag particles" refers to particles containing silver (Ag) element as a main component. That is, the Ag particles may contain a small amount of metal elements other than silver as long as it does not significantly impair the technology disclosed herein. The "metal elements other than silver" here are unavoidable impurities that may be mixed in during the production process of the Ag particles, and are not limited to specific metal elements. For example, the purity of the Ag particles (content of silver element) is preferably 95% or more, more preferably 97% or more, and particularly preferably 99% or more. As the purity of the Ag particles increases, the electrical resistance of the electrode after curing tends to decrease.
[0023] The scale-like Ag particles are flat Ag particles having a thin thickness as a whole. When the thermosetting paste containing the scale-like Ag particles is heated, the scale-like Ag particles are densely arranged on the surface side of the electrode after thermal curing. The electrode with the scale-like Ag particles densely arranged on the surface side has an advantage that the silver exposure rate on the surface is high, and therefore plating on the electrode surface is easy. In addition, when the scale-like Ag particles are used, the Ag particles are easily contacted with each other in the electrode after curing. This makes it easier to form a conductive path in the electrode, which can contribute to reducing the electrical resistance. The average aspect ratio of the scale-like Ag particles is preferably more than 1.5, more preferably 2 or more, even more preferably 2.5 or more, and particularly preferably 3 or more. The scale-like Ag particles having such a large aspect ratio are particularly likely to be arranged on the surface side of the electrode after thermal curing, and therefore the electrical resistance can be more suitably reduced. On the other hand, the upper limit of the average aspect ratio of the scale-like Ag particles is preferably 10, and more preferably 7.5 or less. The "average aspect ratio" here is the average value of the ratio between the thickness and the major axis of a plurality of Ag particles. This average aspect ratio can be measured according to the following procedure. First, a rectangular parallelepiped is drawn circumscribing the Ag particle in a scanning electron microscope photograph (SEM photograph) of the Ag particle to be measured. Next, the aspect ratio is calculated by dividing the long side of this rectangular parallelepiped by the thickness (shortest side) (long side / thickness). The average value of the aspect ratios of 50 Ag particles is then taken as the average aspect ratio. This average aspect ratio can be calculated using a conventionally known image analysis software (such as WinROOF manufactured by Mitani Shoji Co., Ltd.).
[0024] Next, in the thermosetting paste disclosed herein, the D of the scale-like Ag particles 50 The particle size is set to 4μm or more. D 50 Since it is difficult for scaly Ag particles with a small particle size to contact each other and to float to the electrode surface during heating, they tend not to exhibit a resistance reduction effect. 50The particle size is preferably 4.2 μm or more, more preferably 4.5 μm or more, further preferably 4.7 μm or more, and particularly preferably 4.9 μm or more. 50 Since scale-like Ag particles having a particle size of 100 nm are also difficult to float to the electrode surface, they tend not to exhibit a resistance reducing effect. 50 The particle size is set to 10 μm or less. From the viewpoint of more suitably reducing the electrical resistance of the electrode, the D of the scale-like Ag particles is set to 10 μm or less. 50 The particle size is preferably 9.7 μm or less, more preferably 9.5 μm or less, further preferably 9 μm or less, and particularly preferably 8.9 μm or less. 50 "Particle size" is the particle size that corresponds to the smallest cumulative 50% particle size in the volume-based particle size distribution based on the laser diffraction / scattering method.
[0025] In addition, in the thermosetting paste disclosed herein, the content of the scaly Ag particles is set to 30 parts by weight or more when the total weight of the Ag particles is 100 parts by weight. This allows the resistance reducing effect of the scaly Ag particles to be properly exhibited. From the viewpoint of further reducing the electrical resistance of the electrode after curing, the content of the scaly Ag particles is preferably 32 parts by weight or more, more preferably 35 parts by weight or more, even more preferably 37 parts by weight or more, and particularly preferably 40 parts by weight or more. On the other hand, in the thermosetting paste disclosed herein, the content of the scaly Ag particles relative to the total weight of the Ag particles is set to 80 parts by weight or less (preferably 79 parts by weight or less, more preferably 77 parts by weight or less, even more preferably 76 parts by weight or less, and particularly preferably 75 parts by weight or less). As will be described in detail later, this allows the adhesiveness improving effect of the spherical Ag particles to be properly exhibited.
[0026] In addition, the scaly Ag particles preferably have an ignition loss (Ig-loss) of 0.5 wt% or less. The ignition loss is the mass loss ratio (%) when the Ag particles are heated from room temperature to 600°C, and can be measured according to the test method for loss and residue of chemical products specified in JIS K 0067:1992. The ignition loss is an index showing the amount of organic components attached to the surface of the Ag particles. For example, the scaly Ag particles may have an organic dispersant applied to the particle surface to suppress the aggregation of the particles. However, this organic dispersant may be a factor that deteriorates the compatibility with the epoxy resin. In this case, the moldability of the paste is reduced, and the surface smoothness of the electrode after curing may be reduced. From this viewpoint, the ignition loss of the scaly Ag particles is preferably 0.5 wt% or less (more preferably 0.48 wt% or less, even more preferably 0.44 wt% or less, and particularly preferably 0.42 wt% or less). On the other hand, the lower limit of the ignition loss of the scaly Ag particles is not particularly limited, and may be 0.1 wt% or more, 0.12 wt% or more, 0.15 wt% or more, or 0.17 wt% or more.
[0027] The tap density of the scaly Ag particles is preferably 3.6 g / ml or more, more preferably 3.8 g / ml or more, even more preferably 4 g / ml or more, and particularly preferably 4.2 g / ml or more. The tap density is an index showing the bulk density in a state where voids formed in the powder naturally filled in a container are eliminated by tapping (light impact). It has been confirmed that when the tap density of the scaly Ag particles increases, the wettability between the Ag particles and the thermosetting component improves, and the moldability of the paste improves. On the other hand, the upper limit of the tap density of the scaly Ag particles is not particularly limited, and may be 7 g / ml or less, 6 g / ml or less, or 5.7 g / ml or less. In this specification, the "tap density" is a measured value when the tapping conditions are tap height: 5 cm, tap speed: 100 times / min, and tapping frequency: 1000 times. The tap density can be measured in accordance with the metal powder tap density measurement method specified in JIS Z 2512:2012.
[0028] The specific surface area of the scale-like Ag particles is 0.3 m2 / g or more is preferable, and 0.34m 2 / g or more is more preferable, and 0.38m 2 / g or more is more preferable, and 0.4m 2 / g or more is particularly preferred. As the specific surface area of the scaly Ag particles increases, the contact area between the scaly Ag particles increases, and the electrical resistance of the electrode after thermal curing tends to decrease. On the other hand, the specific surface area of the scaly Ag particles is preferably 0.65 m 2 / g or less is preferable, and 0.6m 2 / g or less is more preferable, and 0.55m 2 / g or less is particularly preferred. When the specific surface area of the scaly Ag particles is reduced, the scaly Ag particles can be prevented from agglomerating together in the paste before heat curing. This can improve the moldability of the paste. Note that the "BET specific surface area" in this specification is a value calculated based on the BET method in accordance with the "Method for measuring the specific surface area of powder (solid) by gas adsorption" specified in JIS Z 8830:2013 (ISO9277:2010).
[0029] (B) Spherical Ag particles The spherical Ag particles are spherical or nearly spherical Ag particles. As described above, when the thermosetting paste disclosed herein is heated, the scaly Ag particles float to the surface side of the electrode. At this time, the mixture of the spherical Ag particles and the thermosetting component becomes the main component on the bottom side of the electrode (the region close to the substrate). This makes it easier for the Ag particles to be bonded to the substrate via the epoxy resin, improving the adhesiveness of the electrode. The average aspect ratio of the spherical Ag particles is preferably 1.5 or less, more preferably 1.2 or less, and even more preferably 1.1 or less. This can further improve the adhesiveness of the electrode. On the other hand, the lower limit of the average aspect ratio of the spherical Ag particles is not particularly limited and may be 1 or more.
[0030] Next, in the thermosetting paste disclosed herein, the D of spherical Ag particles 50The particle size is set to 1.5 μm or more. This prevents a plurality of spherical Ag particles from agglomerating together, and prevents a decrease in the contact area between the spherical Ag particles and the thermosetting component due to the formation of agglomerated particles. As a result, the adhesion of the electrode to the substrate can be further improved. From the viewpoint of further improving the adhesion of the electrode, the D of the spherical Ag particles is set to 1.5 μm or more. 50 The particle size is preferably 1.6 μm or more, more preferably 1.7 μm or more, further preferably 1.8 μm or more, and particularly preferably 1.9 μm or more. On the other hand, the D of the spherical Ag particles 50 The upper limit of the particle size is not particularly limited, and may be 2.5 μm or less, 2.4 μm or less, 2.3 μm or less, 2.2 μm or less, or 2.1 μm or less.
[0031] In addition, in the thermosetting paste disclosed herein, the BET specific surface area of the spherical Ag particles is 0.5 m 2 / g or less. If the BET specific surface area of the spherical Ag particles becomes too large, the aggregation of the spherical Ag particles is promoted, and the adhesion of the electrode may decrease. From the viewpoint of suppressing the aggregation of the spherical Ag particles, the BET specific surface area of the spherical Ag particles is set to 0.48 m 2 / g or less is preferable, and 0.46m 2 / g or less is more preferable, and 0.44m 2 / g or less is particularly preferred. The lower limit of the BET specific surface area of the spherical Ag particles is not particularly limited. For example, the BET specific surface area of the spherical Ag particles is preferably 0.05 m 2 / g or more, 0.1m 2 / g or more, 0.15m 2 / g or more, 0.2m 2 / g or more, 0.25m 2 / g or more, 0.3m 2 / g or more.
[0032] In the thermosetting paste disclosed herein, as described above, the content of the scaly Ag particles relative to the total weight of the Ag particles is set to 80 parts by weight or less. That is, in the thermosetting paste disclosed herein, the content of the spherical Ag particles relative to the total weight of the Ag particles is 20 parts by weight or more. This allows the above-mentioned adhesiveness improving effect of the spherical Ag particles to be properly exhibited. The content of the spherical Ag particles is preferably 21 parts by weight or more, more preferably 23 parts by weight or more, even more preferably 24 parts by weight or more, and particularly preferably 25 parts by weight or more. This allows the adhesiveness improving effect of the spherical Ag particles to be properly exhibited.
[0033] The tap density of the spherical Ag particles is preferably 5 g / ml or more, more preferably 5.2 g / ml or more, even more preferably 5.4 g / ml or more, and particularly preferably 5.6 g / ml or more. It has been confirmed that the fixation of the electrode improves as the tap density of the spherical Ag particles increases. On the other hand, the upper limit of the tap density of the spherical Ag particles is not particularly limited, and may be 7 g / ml or less, 6 g / ml or less, or 5.6 g / ml or less.
[0034] The ignition loss (Ig-loss) of the spherical Ag particles is preferably 0.7 wt% or less, more preferably 0.68 wt% or less, even more preferably 0.67 wt% or less, and particularly preferably 0.66 wt% or less. As with the above-mentioned scaly Ag particles, the moldability of the paste tends to improve as the ignition loss (amount of attached organic components) decreases. On the other hand, the lower limit of the ignition loss of the spherical Ag particles is not particularly limited, and may be 0.1 wt% or more, 0.12 wt% or more, 0.15 wt% or more, or 0.17 wt% or more.
[0035] (C) Thermosetting component In this specification, the term "thermosetting component" is a concept that includes a thermosetting resin, a curing agent, and a curing accelerator. The thermosetting component is an organic compound (excluding a silane coupling agent described later) that contributes to the thermosetting of the thermosetting paste and remains on the electrode after curing. The thermosetting component of the thermosetting paste disclosed herein will be described below.
[0036] (C-1) Thermosetting resin The thermosetting paste disclosed herein contains an epoxy resin as a thermosetting resin. The epoxy resin is a resin having an epoxy group. By heating this epoxy resin at a predetermined temperature (for example, 200°C or higher), a crosslinked network in which the epoxy groups are bonded to each other is generated. This causes the thermosetting paste to be thermally cured, so that an electrode can be formed on a substrate. In the thermosetting paste disclosed herein, a novolac type epoxy resin is used. First, examples of the novolac type epoxy resin include phenol novolac type epoxy resin, cresol novolac type epoxy resin, naphthol novolac type epoxy resin, naphthol-phenol co-condensed novolac type epoxy resin, and naphthol-cresol co-condensed novolac type epoxy resin. The thermosetting paste may contain two or more of these novolac type epoxy resins. In addition, there are epoxy resins that are liquid at 25°C (liquid epoxy resins) and epoxy resins that are solid at 25°C (solid epoxy resins). According to the inventor's experiments, it has been confirmed that, among the above-mentioned novolac type epoxy resins, the novolac type epoxy resin that is solid at 25°C improves the glass transition point of the electrode after thermal curing. This makes it possible to suppress the deformation of the electrode in a high-temperature environment, thereby improving the high-temperature reliability of the electrode. The content of the novolac type epoxy resin can be determined based on the number of epoxy groups contained in the novolac type epoxy resin and the content of the curing agent and curing accelerator described below.
[0037] (C-2) Hardener The curing agent is an organic compound having a reactive group that reacts with the thermosetting resin. In the thermosetting paste disclosed herein, the thermosetting component contains a curing agent. This makes it possible to prevent a decrease in adhesion due to poor curing. As described above, the thermosetting paste disclosed herein contains an epoxy resin as the thermosetting resin, so a curing agent that reacts with the epoxy group of the epoxy resin is used. An example of a curing agent that reacts with this epoxy group is a phenol-based curing agent. Specific examples of such phenol-based curing agents include novolac-type phenolic resins such as phenol novolac resin, cresol novolac resin, bisphenol novolac resin, and phenol-biphenyl novolac resin. Another example of the curing agent is a urea-based curing agent. Specific examples of such urea-based curing agents include dimethyl urea, trimethyl urea, ethyl dimethyl urea, cyclohexyl dimethyl urea, dichlorophenyl dimethyl urea, chloromethylphenyl dimethyl urea, methylphenyl dimethyl urea, methylphenyl dimethyl urea, and dimethylphenyl dimethyl urea. The curing agent may contain two or more of the above-mentioned components.
[0038] In addition, the content of the curing agent is preferably adjusted in accordance with the relationship between the number of epoxy groups of the epoxy resin and the number of reactive groups of the curing agent. For example, in the case of a phenol-based curing agent, the hydroxyl group in the molecule becomes a reactive group and reacts with the epoxy group of the epoxy resin. For this reason, it is preferable that the phenol-based curing agent is added in an amount of 30 hydroxyl equivalent parts or more (more preferably 40 hydroxyl equivalent parts or more) relative to the epoxy equivalent (100 epoxy groups) of the epoxy resin. This makes it easier to heat-cure the epoxy resin. On the other hand, in consideration of the adverse effect of remaining curing agent that does not contribute to the curing reaction, it is preferable that the phenol-based curing agent is added in a ratio of 100 hydroxyl equivalent parts or less relative to the epoxy equivalent of the epoxy resin.
[0039] (C-3) Curing accelerator The curing accelerator is an additive that accelerates the reaction between the curing agent and the thermosetting resin. In the thermosetting paste disclosed herein, the thermosetting component contains a curing accelerator, so that the deterioration of adhesiveness due to poor curing can be reliably prevented. Specific examples of the curing accelerator include guanidine-based curing accelerators and amine-based curing accelerators. For example, guanidine-based curing accelerators include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide. Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene. The curing accelerator may contain two or more of the above-mentioned components. The content of the curing accelerator is preferably 0.14 to 0.8 parts by weight, more preferably 0.2 to 0.5 parts by weight, based on the total amount (100 parts by weight) of the epoxy resin.
[0040] (C-4) Total amount of thermosetting components The thermosetting paste disclosed herein contains 10 parts by weight or more of the thermosetting component (C) relative to the total weight (100 parts by weight) of the Ag particles. This can prevent a decrease in adhesiveness due to a shortage of the thermosetting component. From the viewpoint of further improving the fixation of the electrode, the content of the thermosetting component relative to the Ag particles is preferably 10.5 parts by weight or more, more preferably 11 parts by weight or more. On the other hand, if the content of the thermosetting component relative to the Ag particles is increased too much, the number of contacts between the Ag particles decreases, making it difficult to form a conductive path in the electrode. From this viewpoint, in the thermosetting paste disclosed herein, the content of the thermosetting component relative to the Ag particles is set to 15 parts by weight or less. From the viewpoint of further reducing the electrical resistance of the electrode, the content of the thermosetting component is preferably 14.5 parts by weight or less, particularly preferably 14 parts by weight or less.
[0041] (D) Silane coupling agent Silane coupling agents are additives that bond to both Ag particles and epoxy resins to improve the adhesion of electrodes. Specifically, silane coupling agents are organosilicon compounds having a functional group X that reacts and bonds with Ag particles and a functional group Y that reacts and bonds with epoxy resins. Examples of functional groups X that bond with Ag particles include alkoxy groups and acetoxy groups. These functional groups X generate silanols by hydrolysis and react and bond with Ag particles. Meanwhile, in the thermosetting paste disclosed herein, a sulfide-based silane coupling agent is used. This sulfide-based silane coupling agent has a polysulfide group as the functional group Y that reacts and bonds with epoxy resins. According to the inventor's experiments, it has been confirmed that this sulfide-based silane coupling agent has a heterogeneous effect of reducing the resistance of the electrode after curing in addition to the general effect of improving adhesion. It is expected that this resistance reduction effect occurs when the sulfide-based silane coupling agent increases the contact points between Ag particles.
[0042] Examples of the sulfide-based silane coupling agent include bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(4-triethoxysilylbutyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(2-triethoxysilylethyl)trisulfide, bis(4-trimethoxysilylbutyl)trisulfide, bis(3-triethoxysilylpropyl)tetrasulfide, Examples of the sulfide-based silane coupling agents include bis(2-triethoxysilylpropyl) disulfide, bis(4-triethoxysilylbutyl) disulfide, bis(3-trimethoxysilylpropyl) disulfide, bis(2-trimethoxysilylethyl) disulfide, bis(4-trimethoxysilylbutyl) disulfide, 3-trimethoxysilylpropyl-N,N-dimethylthiocarbamoyl tetrasulfide, and 2-triethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide. One of these sulfide-based silane coupling agents may be used alone, or two or more may be mixed. The silane coupling agent may contain a silane coupling agent other than the sulfide-based silane coupling agent, as long as it does not significantly exhibit the effects of the technology disclosed herein (especially the reduction in potential resistance).
[0043] The thermosetting paste disclosed herein contains 0.1 parts by weight or more of a sulfide-based silane coupling agent relative to the total weight (100 parts by weight) of the Ag particles. This allows the resistance reduction effect and fixation improvement effect of the sulfide-based silane coupling agent to be appropriately generated. The content of the sulfide-based silane coupling agent relative to the total weight of the Ag particles is preferably 0.11 parts by weight or more, more preferably 0.12 parts by weight or more, even more preferably 0.13 parts by weight or more, and particularly preferably 0.15 parts by weight or more. This allows the formation of an electrode with lower electrical resistance and better adhesion to the substrate. On the other hand, if the content of the sulfide-based silane coupling agent is increased too much, the content of the Ag particles is relatively decreased, and there is a risk that the electrical resistance will increase instead. From this viewpoint, in the thermosetting paste disclosed herein, the content of the sulfide-based silane coupling agent relative to the Ag particles is set to 0.6 parts by weight or less. In addition, from the viewpoint of further reducing the electrical resistance of the electrode, the content of the sulfide-based silane coupling agent is preferably 0.5 parts by weight or less, more preferably 0.45 parts by weight or less, even more preferably 0.4 parts by weight or less, and particularly preferably 0.38 parts by weight or less.
[0044] (E) Organic solvent The organic solvent is a liquid medium that disperses Ag particles and dissolves the thermosetting component and the silane coupling agent. The organic solvent can be any conventionally known organic solvent that can be used in a conductive paste (typically a thermosetting paste) without any particular limitation, and is not a factor that limits the technology disclosed herein. Examples of the organic solvent include alcohol-based solvents such as terpineol, texanol, dihydroterpineol, and benzyl alcohol; glycol-based solvents such as ethylene glycol and diethylene glycol; glycol ether-based solvents such as diethylene glycol monoethyl ether and butyl carbitol (diethylene glycol monobutyl ether); ester-based solvents such as isobornyl acetate, ethyl diglycol acetate, butyl glycol acetate, butyl diglycol acetate, butyl cellosolve acetate, and butyl carbitol acetate (diethylene glycol monobutyl ether acetate); hydrocarbon-based solvents such as toluene and xylene; and mineral spirits. In consideration of the storage stability of the conductive paste, the boiling point of the organic solvent is preferably about 200° C. or higher.
[0045] As described above, the organic solvent is a component that is removed by heat treatment. Therefore, from the viewpoint of improving the performance (electrical resistance, adhesiveness, high-temperature reliability, etc.) of the electrode after thermal curing, the content ratio of the organic solvent in the thermosetting paste is not limited. It is preferable that the content ratio of the organic solvent is appropriately adjusted so that an electrode of a desired shape is formed, taking into consideration the means for printing (applying) the paste. For example, when the total weight of the paste is 100 parts by weight, the content of the organic solvent is preferably 2 parts by weight to 30 parts by weight, more preferably 4 parts by weight to 20 parts by weight.
[0046] In addition, the thermosetting paste disclosed herein is preferably controlled in terms of paste moldability. The Casson yield value is the shear stress when the shear rate is set to zero in viscosity measurement using a B-type viscometer. As the Casson yield value increases, the stress required when the shape of the paste begins to change increases. A paste with a small Casson yield value has excellent leveling properties after printing (application), and therefore can form an electrode with good dimensional properties. From this viewpoint, the Casson yield value of the thermosetting paste is preferably 120 Pa or less, more preferably 100 Pa or less, and even more preferably 80 Pa or less. On the other hand, the lower limit of the Casson yield value is not particularly limited, and may be 10 Pa or more, or 20 Pa or more. The Casson yield value (paste moldability) can be adjusted by the ignition loss of the Ag particles, the tap density of the scaly Ag particles, the content of the thermosetting component, the structure (type) of the thermosetting component (e.g., epoxy resin), the viscosity of the organic solvent, the content of the organic solvent, and the like.
[0047] The thermosetting paste disclosed herein has been described above. The thermosetting paste disclosed herein is not limited to one containing only the above-mentioned components. That is, the thermosetting paste may further contain a conventionally known additive that can be used in a conductive paste (typically, a thermosetting paste) within a range that does not significantly impair the effect of the technology disclosed herein.
[0048] 2. Uses of thermosetting paste Next, a method for manufacturing an electronic component using the thermosetting paste disclosed herein will be described. In the method for manufacturing an electronic component, for example, the following steps S1 to S4 are performed. Step S1: Preparation of the substrate Step S2: Preparation of thermosetting paste Process S3: Printing process Process S4: Heating process
[0049] (1) Preparation of the substrate In this step, a substrate on which the thermosetting paste is printed is prepared. The type of substrate is not particularly limited, and any conventionally known substrate for electronic components can be used without any particular restriction. The thermosetting paste disclosed herein is hardened by heat treatment at a low temperature (200°C or less) to form an electrode. In view of this, the manufacturing method disclosed herein is particularly suitable for use in the manufacture of electronic components that use substrates with low heat resistance. Examples of such substrates include substrates made of resin, paper, cloth, etc.
[0050] (2) Preparation of thermosetting paste In this step, the thermosetting paste having the above-mentioned configuration is prepared. The detailed configuration of the thermosetting paste is not described again because it would be redundant. This step is not particularly limited as long as a thermosetting paste having the desired components can be prepared. That is, the thermosetting paste may be prepared by mixing the above-mentioned components, or a separately prepared thermosetting paste may be purchased.
[0051] (3)Printing process In this step, the thermosetting paste disclosed herein is printed on a substrate. The specific printing method in this step is not particularly limited. For example, a conventionally known printing method such as screen printing or dip printing can be adopted without any particular limitation. The thickness of the paste printed in this step is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and particularly preferably 20 μm or more. By printing a paste of a certain thickness or more in this way, an electrode with excellent conductivity can be formed. The printing thickness of the paste is preferably 150 μm or less, more preferably 100 μm or less, even more preferably 75 μm or less, and particularly preferably 50 μm or less. This makes it easy to volatilize the organic solvent and remove it from the paste in the heating step described later, thereby suppressing poor forming of the electrode.
[0052] (4)Heating process In this step, the thermosetting paste printed on the substrate is heated. This causes the thermosetting paste to be thermally cured, and an electrode having a desired shape is formed on the substrate. In this step, it is preferable to carry out a first heating treatment (drying treatment) at a temperature at which the organic solvent volatilizes and the epoxy resin does not thermally cure, and a second heating treatment (thermosetting treatment) at a temperature at which the epoxy resin is thermally cured, in a stepwise manner. This allows the epoxy resin to be thermally cured after a high-density dry film is formed from the organic solvent being sufficiently volatilized. As a result, the number of contact points between the Ag particles is further increased, and the electrical resistance of the electrode after curing can be further reduced. Specifically, the heating temperature in the first heating treatment (drying treatment) is preferably 80°C to 180°C, more preferably 100°C to 150°C. The heating time in the first heating treatment (drying treatment) is preferably 5 minutes to 60 minutes, more preferably 10 minutes to 30 minutes. On the other hand, the heating temperature in the second heating treatment (thermal curing treatment) is preferably 150° C. to 250° C., more preferably 180° C. to 230° C. The heating time in the second heating treatment (thermal curing treatment) is preferably 15 minutes to 90 minutes, more preferably 30 minutes to 60 minutes.
[0053] When the thermosetting paste disclosed herein is used, the scaly Ag particles rise to the surface of the paste during the heating process. This allows the scaly Ag particles to be densely arranged on the surface of the electrode after thermal curing, reducing the electrical resistance. In addition, in the thermosetting paste disclosed herein, the D 50 Since the particle size is 4 μm or more, the scaly Ag particles are more likely to float. This can further reduce the electrical resistance of the electrode after curing. In addition, as a result of the floating of the scaly Ag particles, the mixture of the spherical Ag particles and the thermosetting component becomes the main component on the bottom side of the electrode. This can improve the adhesion of the electrode to the substrate. In addition, the spherical Ag particles of the thermosetting paste disclosed herein have a D 50 The particle size is 1.5 μm or more, and the BET specific surface area is 0.5 m 2 / g or less. This makes it possible to suppress the aggregation of the spherical Ag particles, thereby more appropriately improving the adhesion of the electrode to the substrate. In the thermosetting paste disclosed herein, the content of the scaly Ag particles relative to the total weight of the Ag particles is set to 30 parts by weight or more and 80 parts by weight or less. This makes it possible to achieve a high level of both the resistance reducing effect of the scaly silver particles and the adhesiveness improving effect of the spherical Ag particles.
[0054] In addition, in the thermosetting paste disclosed herein, a novolac type epoxy resin that is solid at 25°C is used as the thermosetting resin. An electrode containing an epoxy resin of this configuration has a high glass transition point after thermal curing, and therefore has excellent high-temperature reliability. In the thermosetting paste disclosed herein, the content of the thermosetting component relative to the total weight of the Ag particles is set to 10 parts by weight or more and 15 parts by weight or less. This makes it possible to sufficiently improve the adhesiveness while suppressing an increase in electrical resistance. In the thermosetting paste disclosed herein, a sulfide-based silane coupling agent is included. The sulfide-based silane coupling agent not only improves the adhesiveness of the electrode after curing, but also contributes to reducing the electrical resistance. In the thermosetting paste disclosed herein, the content of the sulfide-based silane coupling agent relative to the total weight of the Ag particles is set to 0.1 parts by weight or more and 0.6 parts by weight or less. This makes it possible to achieve a well-balanced effect of reducing resistance and improving adhesiveness by the sulfide-based silane coupling agent.
[0055] As described above, the thermosetting paste disclosed herein makes it possible to manufacture high-performance electronic components that are excellent in terms of electrical resistance, high-temperature reliability, and adhesiveness.
[0056] [Test example] Test examples relating to the technology disclosed herein will be described below. Note that the technology disclosed herein is not limited to the test examples described below.
[0057] <First test> 1. Thermosetting paste components In this test example, 29 kinds of thermosetting pastes (Examples 1 to 12 and Comparative Examples 1 to 17) were prepared. Each of the thermosetting pastes prepared in this test contains scaly Ag particles, spherical Ag particles, a thermosetting component, a silane coupling agent, an organic solvent, a curing agent, and a curing accelerator. The specific components are described below.
[0058] (1) Scale-like Ag particles In this test, the scaly Ag particles were any of the seven types of Ag particles shown in Table 1 below. The type and content of the scaly Ag particles used in each example are shown in Tables 3 to 5 below.
[0059] [Table 1]
[0060] (2) Spherical Ag particles In this test, one of the two types of Ag particles shown in Table 2 was used as the spherical Ag particles. The type and content of the spherical Ag particles used in each example are shown in Tables 3 to 5 below.
[0061] [Table 2]
[0062] (3) Thermosetting component (3-1) Epoxy resin In this test, the following eight types of epoxy resins were used as the thermosetting resin. The types of epoxy resins used in each example are shown in Tables 3 to 5 below. [Type of epoxy resin] Resin 1: Cresol novolac epoxy resin (solid at 25°C) Epoxy equivalent: 214g / eq. Resin 2: Phenol novolac type epoxy resin (solid at 25°C) Epoxy equivalent: 175g / eq. Resin 3: Phenol novolac type epoxy resin (liquid at 25°C) Epoxy equivalent: 175g / eq. Resin 4: Bisphenol F epoxy resin (liquid at 25°C) Epoxy equivalent: 170g / eq. Resin 5: Bisphenol A epoxy resin (solid at 25°C) Epoxy equivalent: 2100g / eq. Resin 6: Bisphenol F type epoxy resin (solid at 25°C) Epoxy equivalent: 2145g / eq. Resin 7: Dicyclopentadiene type epoxy resin (solid at 25°C) Epoxy equivalent: 259g / eq. Resin 8: Naphthalene type epoxy resin (solid at 25°C) Epoxy equivalent: 165g / eq.
[0063] (3-2) Other thermosetting components In addition, in this test, a curing agent and a curing accelerator were used as the thermosetting components other than the epoxy resin. Novolac phenolic resin and dichlorophenyl dimethyl urea were used as the curing agents. The amount of novolac phenolic resin added was set to 3.2 parts by weight, and the amount of dichlorophenyl dimethyl urea added was set to 0.18 parts by weight when the total amount of Ag particles was 100 parts by weight. Dicyandiamide was used as the curing accelerator. The amount of the curing accelerator (dicyandiamide) added was set to 0.28 parts by weight when the total amount of Ag particles was 100 parts by weight. The content of the thermosetting components in each example (total content of epoxy resin, curing agent, and curing accelerator) is shown in Tables 3 to 5 below.
[0064] (4) Silane coupling agents In this test, the following four types of silane coupling agents were prepared: The type and content of the silane coupling agent used in each example are shown in Tables 3 to 5 below. [Types of silane coupling agents] SC1: Bis(3-triethoxysilylpropyl)tetrasulfide SC2: Bis(3-triethoxysilylpropyl) disulfide SC3: 3-glycidoxypropyltrimethoxysilane SC4: 3-aminopropyltriethoxysilane
[0065] (5) Organic solvents In this test, butyl carbitol was used as the organic solvent, and the content of the organic solvent (butyl carbitol) was set to 7.8 parts by weight when the total amount of Ag particles was 100 parts by weight.
[0066] 2. Paste Preparation Procedure In this test, first, an organic solvent, an epoxy resin, and a novolac-type phenolic resin (hardening agent) were mixed. Then, this mixture was heated at 100°C for 24 hours and then cooled to room temperature. In this way, an organic vehicle in which the epoxy resin and the novolac-type phenolic resin were dissolved in the organic solvent was obtained. Next, scaly Ag particles, spherical Ag particles, a silane coupling agent, dichlorophenyldimethylurea (hardening agent), and dicyandiamide (hardening accelerator) were added to this organic vehicle, and kneaded with a three-roll mill. In this way, the thermosetting paste of each example was prepared.
[0067] 3.Evaluation Test In this test, electrodes were formed on a substrate using the thermosetting paste of each example, and then the electrical resistance, adhesiveness, and high-temperature reliability of the electrodes were evaluated.
[0068] (1) Evaluation of electrical resistance In this evaluation, first, the 29 types of thermosetting pastes described above were each printed on the surface of a substrate by screen printing. The substrate used in this test was a glass substrate (Matsunami Glass Industry Co., Ltd.) with an upper surface area of 20 mm x 20 mm. In addition, in the screen printing, a metal mask with a thickness of 50 μm and an opening of 20 mm x 20 mm was used, and a metal squeegee was used, and the printing speed was set to 30 mm / sec. In this test, the printing thickness of the paste was set to about 25 μm, and a printed film with a square shape in a plan view was formed.
[0069] Next, the substrate after the paste printing was subjected to a first heating treatment (drying treatment) at 130°C for 15 minutes. This resulted in a dry film in which the organic solvent was removed from the paste. Then, a second heating treatment (resin curing treatment) was performed at 180°C for 60 minutes to thermally cure the epoxy resin in the dry film.
[0070] In this evaluation, the electrical resistance of the electrodes after thermal curing was evaluated. The specific evaluation procedure is as follows. First, the film thickness of the electrodes was measured using a surface roughness meter (Surfcom, manufactured by Tokyo Seimitsu Co., Ltd.). Next, the sheet resistance of the electrodes after thermal curing was measured by the four-probe method using a resistivity meter (model: Loresta GX MCP-T700) manufactured by Mitsubishi Chemical Analytech Co., Ltd. Then, the electrical resistance (Ω·cm) of the electrodes for each example was measured by multiplying the film thickness and the sheet resistance. In this test, the electrical resistance was measured when the electrical resistance was 1×10 -4 Examples with a resistance of Ω·cm or less were rated as "◎" and those with a resistance of 1×10 -4 Ωcm super 5×10 -4 Examples with a resistance of less than 5×10 -4 The cases where the resistance was Ω·cm or more were evaluated as “×”.
[0071] (2) Evaluation of adhesion In this evaluation, the adhesiveness of the electrodes after thermal curing was evaluated. The specific evaluation procedure is as follows. First, the 29 types of thermosetting pastes described above were printed on the surface of the substrate by screen printing. The printing conditions at this time were set to the same conditions as those in "(1) Evaluation of Electrical Resistance" above. Next, an alumina chip measuring 2 mm x 2 mm was placed on the paste printed (applied) on the glass substrate, and a first heat treatment (drying treatment) was performed at 130°C for 15 minutes. Then, a second heat treatment (resin curing treatment) was performed at 180°C for 60 minutes to form a cured film (electrode) with the alumina chip adhered to the upper surface. Then, a load was applied to the alumina chip using a 4000 universal bond tester manufactured by Nordson DAGE, and the strength (peel strength) when the chip peeled off was measured. This resulted in the peel strength (N / mm 2 In this test, the peel strength was measured at 20N / mm 2Examples that were above 20N / mm were rated as "◎" and 2 Less than 10N / mm 2 Examples with a strength of over 10 N / mm were rated as "○" and those with a strength of over 10 N / mm were rated as "○". 2 The following cases were evaluated as "x".
[0072] (3) Evaluation of glass transition temperature In this evaluation, the glass transition temperature was measured. The specific evaluation procedure is as follows. First, the paste was applied onto a resin sheet made of PTFE (polytetrafluoroethylene) using an applicator with a gap set to 150 μm. Next, a first heat treatment (drying treatment) was performed at 130° C. for 15 minutes, and then a second heat treatment (resin curing treatment) was performed at 180° C. for 60 minutes to obtain a cured film. Next, the cured film after the heat treatment was peeled off from the resin sheet and cut into a size of 1 cm x 4 cm. Then, the glass transition temperature of the cured film was measured using a viscoelasticity measuring device (DMA7100) manufactured by Hitachi High-Tech Science Corporation. In the measurement of the glass transition temperature, the temperature was raised to 300° C. at a heating rate of 1° C. / min. And, examples with a glass transition temperature of 200° C. or higher were evaluated as "◎" because it is understood that durability against long-term environmental changes is improved when used in electrodes of electronic components. Also, examples where the temperature was less than 200°C and more than 150°C were evaluated as "○", and examples where the temperature was 150°C or less were evaluated as "×".
[0073] The results of the above-mentioned evaluations are shown in Tables 3 to 5 below.
[0074] [Table 3]
[0075] [Table 4]
[0076] [Table 5]
[0077] As shown in Tables 3 to 5, in Examples 1 to 12, electronic components were produced that were excellent in three performance areas: electrical resistance, adhesiveness, and high-temperature reliability. On the other hand, in Comparative Examples 1 to 17, it was confirmed that at least one of electrical resistance, adhesiveness, and high-temperature reliability was deteriorated. As a result of comparing each example, it was found that the D of the scaly Ag particles had a significant effect on the electrical resistance of the electrode after curing. 50 It was confirmed that the particle size, the content of scale-like Ag particles, the structure of the silane coupling agent, the content of the silane coupling agent, and the content of the thermosetting component have an effect on the adhesion of the electrode. 50 It was confirmed that the particle size, the content of spherical Ag particles, the content of thermosetting components, the structure of the silane coupling agent, and the content of the silane coupling agent have an effect. It was also confirmed that the structure of the epoxy resin and the state of the epoxy resin at room temperature have an effect on the high-temperature reliability of electronic components.
[0078] <Second test> In this test, the paste moldability and the silver exposure rate after thermal curing were evaluated for Examples 1 to 12, which had shown excellent electrode performance in the first test.
[0079] (1) Evaluation of rheological properties In this evaluation, the Casson yield values were measured for the pastes of Examples 1 to 12, and the paste moldability was evaluated based on the measurement results. In this test, examples in which the Casson yield value was 120 Pa or less were evaluated as "◎", and examples in which the Casson yield value was more than 120 Pa were evaluated as "×".
[0080] (2) Evaluation of silver exposure rate In this evaluation, cured films (electrodes) were prepared using the pastes of Examples 1 to 12 according to the same procedure as in "(1) Evaluation of Electrical Resistance" in the first test. Then, the silver exposure rate on the surface of the prepared electrode was measured. The specific evaluation procedure is as follows. First, the surface of the electrode after thermal curing was observed (for example, at a magnification of 2,000 times) using a field emission scanning electron microscope (FE-SEM) to obtain an observation image. Next, the area of the silver particles in the observation image was calculated. Then, the silver exposure rate (%) on the surface of the electrode of each example was measured by dividing the area of the silver particles by the area of the observation range. Then, in this test, examples in which the silver exposure rate was 70% or more were evaluated as "◎", examples in which the silver exposure rate was less than 70% and more than 60% were evaluated as "○", and examples in which the silver exposure rate was 60% or less were evaluated as "×".
[0081] The results of each of the above evaluations are shown in Table 6 below.
[0082] [Table 6]
[0083] As shown in Table 6, in addition to the three performances mentioned above, Examples 1 to 10 were confirmed to have excellent paste moldability. Furthermore, as a result of comparing Examples 1 to 10 with Examples 11 and 12, it was found that the moldability (Casson's yield value) of the thermosetting paste is affected by the tap density and ignition loss (Ig-loss) of the scaly Ag particles. In addition, it was confirmed that Examples 1 to 12 all have an excellent silver exposure rate. From this, it can be seen that the silver exposure rate of the electrode is related to the D of the scaly Ag particles, as well as the electrical resistance measured in the first test. 50 It is expected that the particle size, the content of scaly Ag particles, the structure of the silane coupling agent, the content of the silane coupling agent, and the content of the thermosetting component have an effect.
[0084] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above.
Claims
1. At least, the composition includes (A) scaly Ag particles, (B) spherical Ag particles, (C) a thermosetting component, (D) a silane coupling agent, and (E) an organic solvent; The (A) scaly Ag particles are In the volume-based particle size distribution based on the laser diffraction / scattering method, the D 50 The particle size is 4 μm or more and 10 μm or less, and The content of Ag particles is 30 parts by weight or more and 80 parts by weight or less when the total weight of the Ag particles is 100 parts by weight, The (B) spherical Ag particles are The above D 50 The particle size is 1.5 μm or more and 2.5 μm or less, and BET specific surface area is 0.5m 2 / g or less, The (C) thermosetting component is A novolac type epoxy resin that is solid at 25° C., a curing agent, and a curing accelerator, the content of the Ag particles is 10 parts by weight or more and 15 parts by weight or less when the total weight of the Ag particles is 100 parts by weight, The silane coupling agent (D) is A silane coupling agent having a polysulfide group, The content of the Ag particles is 0.1 parts by weight or more and 0.6 parts by weight or less when the total weight of the Ag particles is 100 parts by weight. A thermosetting paste comprising:
2. The thermosetting paste according to claim 1 , wherein the (A) scaly Ag particles have an average aspect ratio of more than 1.5 and not more than 10.
3. 3. The thermosetting paste according to claim 1, wherein the scaly Ag particles (A) have an ignition loss (Ig-loss) of 0.5 wt % or less when heated from room temperature to 600°C.
4. The thermosetting paste according to any one of claims 1 to 3, wherein the (A) scaly Ag particles have a tap density of 4 g / ml or more and 7 g / ml or less.
5. The thermosetting paste according to any one of claims 1 to 4, wherein the spherical Ag particles (B) have an average aspect ratio of 1 or more and 1.5 or less.
6. The thermosetting paste according to any one of claims 1 to 5, wherein the (B) spherical Ag particles have a tap density of 5 g / ml or more and 7 g / ml or less.
7. The thermosetting paste according to any one of claims 1 to 6, wherein the novolac type epoxy resin comprises at least one selected from the group consisting of phenol novolac type epoxy resins, cresol novolac type epoxy resins, naphthol novolac type epoxy resins, naphthol-phenol co-condensed novolac type epoxy resins, and naphthol-cresol co-condensed novolac type epoxy resins.
8. The (D) silane coupling agent is, for example, bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(4-triethoxysilylbutyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(2-triethoxysilylethyl)trisulfide, bis(4-trimethoxysilylbutyl)trisulfide, bis(3-triethoxysilylpropyl)disulfide, bis(2-triethoxysilylethyl)trisulfide, 8. The thermosetting paste according to claim 1, comprising at least one selected from the group consisting of bis(4-triethoxysilylethyl) disulfide, bis(4-triethoxysilylbutyl) disulfide, bis(3-trimethoxysilylpropyl) disulfide, bis(2-trimethoxysilylethyl) disulfide, bis(4-trimethoxysilylbutyl) disulfide, 3-trimethoxysilylpropyl-N,N-dimethylthiocarbamoyl tetrasulfide, and 2-triethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide.
9. The thermosetting paste according to any one of claims 1 to 8, having a Casson yield value at 25°C of 120 Pa or less.
Citation Information
Patent Citations
Method and device for producing battery plate group
JP1977081529A
Seat fixing structure of wheel chair in car
JP1985092754A
Method for producing liquid resin composition, liquid resin composition, and semiconductor device
JP2008106160A
Thermosetting conductive paste composition
JP2013196954A
Resin composition
JP2014196437A